Respuesta :
x^2 - 12x - 5 = 7
x^2 - 12x = 7 + 5
x^2 - 12x = 12
x^2 - 12x + 36 = 12 + 36
(x - 6)^2 = 48 <====
x^2 - 12x = 7 + 5
x^2 - 12x = 12
x^2 - 12x + 36 = 12 + 36
(x - 6)^2 = 48 <====
Answer:
The completing square form of given equation is [tex](x-6)^2=48[/tex]
Step-by-step explanation:
Given: [tex]x^2-12x-5=7[/tex]
We need to change given quadratic equation in completing square form.
[tex](x-p)^2=q[/tex]
[tex]x^2-12x-5=7[/tex]
First we add 5 both sides
[tex]x^2-12x-5+5=7+5[/tex]
Add both sides square of half of coefficient of x
[tex]x^2-12x+36=36+12[/tex]
[tex](x-6)^2=48[/tex]
Now we compare the equation to completing square
[tex](x-p)^2=q\rightarrow (x-6)^2=48[/tex]
[tex]p\rightarrow 6[/tex]
[tex]q\rightarrow 48[/tex]
Hence, The completing square form of given equation is [tex](x-6)^2=48[/tex]